Graze : inspiration for small plates and meandering meals - Lenzer, Suzanne (Rodale, 2017)
In Graze, Suzanne dreams up lush as well as simple concoctions from everyday ingredients, taking full advantage of her pantry, fridge, and freezer. Graze is a lesson in shopping as well as cooking. Using the best that markets have to offer and with minimal effort, Suzanne dazzles us with endless combinations and stunning pictures, creating interesting and delectable small plates.